DEVELOPMENT OF INNOVATIVE INSTRUCTIONAL LEADERSHIP MEASUREMENT MODEL IN TECHNICAL AND VOCATIONAL SYSTEM - Mat Nashir, Irdayanti; Mustapha, Ramlee (Journal of Human Capital Development (JHCD), 2018)
This study aimed to determine the constructs and to develop measurement model of innovative instructional leadership for polytechnics system in Malaysia. This study has utilized a model development approach as its research design. In the earlier stage, a Modified Delphi technique was used to gather initial data regarding innovative instructional leadership. Eleven experts were selected based on their expertise and experience. They confirmed 3 constructs of innovative instructional leadership for the polytechnics system. Stratified random sampling was used in this study to select the respondents. A new instrument was developed which consisted of 3 constructs and 12 items and distributed to the respondents in the selected polytechnics to determine the innovative instructional leadership of the polytechnic administrators. Empirical data collected were analyses using descriptive and inferential statistics that included confirmatory factor analysis. The results showed that lecturers at the polytechnics did not agree that their administrators possess the innovative instructional leadership and also found that the administrators of the polytechnics have moderate level of innovative instructional leadership for most of the constructs. Based on confirmatory factor analysis, it was found that only 12 items out of 20 items that are important to the innovative instructional leadership in the polytechnics system in Malaysia. It is hoped that the results of this study could assist the top management in polytechnics to spearhead the direction and leadership of the polytechnics towards a more creative and innovative system in line with the government’s desire to transform the polytechnic system to becoming a preferred choice of higher education institution. Keywords: Technical and Vocational Educational Training (TVET), innovative instructional leadership, measurement model, Modified Delphi Technique, Malaysia.